Intellectual Analysis For Educational Path’ Cognitive Modeling: Digital Knowledge forPost-Modern Value Creation - Pokrovskaia, Nadezhda Nikolaevna; Margulyan, Yakov Aronovich; Bulatetskaia, Alena; Snisarenko, Svetlana (Տիգրան Մեծ)
The philosophy of cognition allows humans to better orient in the world due to the deepening and ex-tension of available paths to follow. The cognitive modelling determines the understanding, knowledge creation and reality reflection in a person‘s conscience. The human persons apply the cognitive approach in the logics and ethics, the example to illustrate this refers to the regulative issues related to self-driving cars, the solutions for the making decision and for the responsibility.Philosophy of education is a specific part of the general knowledge about the creation and transfer of knowledge that traditionally allowed scholars the understanding of the cognition process. The digital era gives broader sense to the cognition and the diversity of knowledge to analyze through the philosophical approach and to the synthesis through educational practices as a subject for the philosophical study.The paper presents the longitude results obtained in 2005-2020 of the values that determine the choice of the educational trajectory on the level of the second degree of higher education – Master pro-grams, which are not necessary for the majority of the corporate positions, that allows scholars to analyze this choice as reflecting the free interest of the potential students for their personal cognitive growth.
Keywords: Education